Preparation of Polyaniline/Polypyrrole Thin Films as Electrode in Salt Water Dechlorination - Maryanti; Yusmaniar (Pusat Inovasi Sains, 2022)
Chlorine is a chemical element that is widely used in daily life that require for dechlorination process to prevent the environment. One method that can be used to treat chlorine waste is through dechlorination. During the dechlorination process, electrodes that chemically stable properties are used. This study aims to test the dechlorination of polyaniline (PANI), polypyrrole (PPy), and various compositions of PANI/PPy composite. FTIR shows related functional groups found in PANI, PPy, and PANI/PPy. XRD shows that the PANI formed was in the semicrystalline phase, while PPy was in the amorphous phase. The conductivity test shows that the PANI sample has the highest conductancy value compared to the PPy or PANI/PPy samples. PANI/PPy with composition ratio of 75/25 had the highest difference in conductance values compared to other composites. The highest dechlorination efficiency value occurred in PANI at a voltage of 1.8 V, which was 1.9%. Meanwhile, in PANI/PPy composite, the highest dechlorination efficiency value came from PANI/PPy 75/25, which was 0.97%.